IMPACT OF FINANCIAL INCLUSION IN LOW‐ AND MIDDLE‐INCOME COUNTRIES: A SYSTEMATIC REVIEW OF REVIEWS. (7th May 2020) - Duvendack, Maren; Mader, Philip
Abstract: Financial inclusion programmes seek to increase access to financial services such as credit, savings, insurance and money transfers. Despite a wealth of systematic review evidence, the impacts of financial inclusion are inconclusive. Hence, the first systematic review of systematic reviews was undertaken to synthesize the impacts of financial inclusion interventions on economic, social, gender and behavioural outcomes. Thirty‐two systematic reviews were identified. The headline finding is that impacts are more likely to be positive than negative, but the effects vary, and appear not to be transformative in scope or scale, as they largely occur in the early stages of the causal chain. The effects of financial services on core economic and social poverty indicators are small and inconsistent. There is no evidence for meaningful behaviour‐change outcomes. The effects on women's empowerment appear generally positive, but they depend upon programme features that are often peripheral to the financial service, and cultural and geographical context. Accessing savings opportunities has small but more consistently positive effects for poor people, and bears fewer downside risks for clients than credit. The inconsistent quality of the primary evidence base that formed the basis of their syntheses raises concerns about the reliability of the overall findings.